(untitled) - Rolls, Edmund T.; Edmund T. Rolls; Gustavo Deco (Oxford,New York, 2002)
different levels. Neurophysiological studies, at the single neuron level are required. We need to bring in neuropsychological studies of brain damaged patients in order to understand what different parts of the visual system do, and what each part is needed for. Neuroimaging work can provide valuable information on the locations in the brain where these processes are taking place. Additionally required is an understanding of the biophysical and synaptic properties of neurons to see how the computing elements of the brain work. A knowledge of the anatomical and functional architecture of the cortex further enhances our understanding. Finally, neural computation methods can bring together the evidence to understand how the visual system actually works. Most of the books looking at the topic of vision tend to take a particular approach and exclude the work and data being obtained from studies adopting other approaches
Keywords: Vision; Computational neuroscience; Neuropsychology; Neurophysiology